Universal Media Strategy: Us vs. Them (KULT_online, 2019)
Alparslan Nas’ Media Representations of the Cultural Other in Turkey offers up-to-date analysis of recent media content (advertisements, cartoons, films and TV shows) with the aim to answer whether a center-periphery binary is exploited in contemporary production. Despite some broad statements and weak ties with existing theoretical work, the author clearly demonstrates the interdependence of these two ‚imaginative categories’ through narrative analysis. By elucidating paradoxes of an incredibly turbulent period in Turkey, this short and comprehensible study brings a host of evidence that the center-periphery cultural dichotomy is a strategic instrument for different subjects to strengthen their position in media representations.